2014
DOI: 10.1111/j.1540-4781.2014.12125.x
|View full text |Cite
|
Sign up to set email alerts
|

When Hands Speak Louder Than Words: The Role of Gesture in the Communication, Encoding, and Recall of Words in a Novel Second Language

Abstract: In the interest of clarifying how gesture facilitates L2 word learning, the current study investigates gesture's influence on three interrelated cognitive processes subserving L2 word learning: communication, encoding, and recall. Individuals unfamiliar with Hungarian learned 20 Hungarian words that were either accompanied or unaccompanied by gestures depicting their referents, and taught the meanings of the words to interlocutors who were also unfamiliar with Hungarian. All participants were then tested for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Culturally familiar gestures raised ratings in two of the four evaluationsconfidence and communicative effectiveness-in Experiment 1, and in addition, they positively affected all of the evaluations in Experiment 2, including the lower judgments of nervousness and higher estimates of how long learners had been studying Japanese. The findings that familiar gestures positively influenced speech perception is consistent with literature showing that semantically related speech and gesture improve accuracy of L1 comprehension (Popelka and Berger, 1971;Graham and Argyle, 1975;Kelly et al, 2010;Dahl and Ludvigsen, 2014) and vocabulary retention in L2 learning (Allen, 1995;Sueyoshi and Hardison, 2005;Sime, 2006;Kelly et al, 2009;Morett, 2014), in addition to boosting speech perception when auditory information is moderately degraded (Obermeier et al, 2011;Drijvers and Özyürek, 2017). Adding to this work, the present study demonstrates that the cultural relationship between L2 speech and gesture matters, too.…”
Section: Culturally Familiar Gestures Help Uniformlysupporting
confidence: 91%
See 1 more Smart Citation
“…Culturally familiar gestures raised ratings in two of the four evaluationsconfidence and communicative effectiveness-in Experiment 1, and in addition, they positively affected all of the evaluations in Experiment 2, including the lower judgments of nervousness and higher estimates of how long learners had been studying Japanese. The findings that familiar gestures positively influenced speech perception is consistent with literature showing that semantically related speech and gesture improve accuracy of L1 comprehension (Popelka and Berger, 1971;Graham and Argyle, 1975;Kelly et al, 2010;Dahl and Ludvigsen, 2014) and vocabulary retention in L2 learning (Allen, 1995;Sueyoshi and Hardison, 2005;Sime, 2006;Kelly et al, 2009;Morett, 2014), in addition to boosting speech perception when auditory information is moderately degraded (Obermeier et al, 2011;Drijvers and Özyürek, 2017). Adding to this work, the present study demonstrates that the cultural relationship between L2 speech and gesture matters, too.…”
Section: Culturally Familiar Gestures Help Uniformlysupporting
confidence: 91%
“…Many of the experiments on this topic have focused on how L2 learners attend to information conveyed through the hands when perceiving novel speech sounds (Hannah et al, 2017;Kelly, 2017;Kushch et al, 2018;Baills et al, 2019;Hoetjes et al, 2019) and comprehending new vocabulary (Allen, 1995;Sueyoshi and Hardison, 2005;Sime, 2006;Kelly et al, 2009;Morett, 2014;Morett and Chang, 2015;Baills et al, 2019;Huang et al, 2019). For example, Kelly et al (2009) investigated how semantic congruence of gesture and speech affected the learning of L2 Japanese vocabulary in native English speakers.…”
Section: Hand Gestures and Second Language (L2)mentioning
confidence: 99%
“…Recently, work in the neurosciences has empirically supported such an approach for teaching (García et al, 2019). In addition, research from the L2 classroom has also confirmed the benefit of movement as a way to facilitate the learning of vocabulary either through gesture (Macedonia, 2014;Morett, 2014) or simply watching others enact the meaning of the words (Birdsell, 2021). These studies look at when the language is paired with congruent action.…”
Section: The Present Studymentioning
confidence: 95%
“…Movement, on the other hand, reinforces the learning of pronunciation features. Research has established strong empirical evidence, showing that L2 instructors' use of gestures facilitate their students' language learning process (e.g., Macedonia & Klimesch, ; McCafferty & Stam, ; Morett, ; Smotrova & Lantolf, ). That includes the uptake of target pronunciation features (Smotrova, ) as gesture is closely related to prosody (i.e., stress, rhythm, and intonation) in language acquisition (Nguyen, ).…”
Section: Haptic Pronunciation Instructionmentioning
confidence: 99%